Effect of an Aquatic Endurance Exercise on Mental General Health in Male Elders - Seyyed Sadreddin Shojaeddin; Amir Dadashpoor (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Aquatic exercise is one of the major activities that recommend to elderly people. The purpose of this study was to examine the effects of aquatic endurance exercise on the mental health, physical symptoms, social performance, anxiety and depression of the male elders. Methods & Materials: In this study, 30 male elders were selected and randomly divided into control and experimental groups. First, all subjects completed General Health Questionnaire (GHQ). Then the experimental group received 6 weeks aquatic endurance exercise (three sessions per week) for six weeks and the control group performed their daily routine activities. After the training intervention, both groups again completed the GHQ - 28. Data analysis with paired and independent samples t-test was performed. Results: The results showed that aquatic endurance exercise has significant effect on mental health (P=0.000), physical symptoms (P=0.000), social performance (P=0.000), anxiety (P=0.034) and depression (P=0.000) of the experimental groups, while in the control group who had not participated in aquatic endurance exercises, no significant changes were observed. The results also showed that there is a significant difference (P=0.001) between the average score of mental general health of experimental and control group after the exercise. Conclusion: Based on this study it can be concluded that aquatic endurance exercise has a positive impact to geriatric psychiatric assessment on the mental general health, physical symptoms, social performance, anxiety and depression.